The Concept of A Religious Humanis Values Education - Hamam Burhanuddin (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2018)
the study in this paper discusses the concept of a religious Humanist Values Education. Islam never experienced a heyday into the study of various disciplines, this is evident by the presence of muslim scientists. But with the passage of time that Islamic intelektualisme begin to Dim along with the understanding and the culture of taqlid. Whereas the Qur'an gave instructions in order to examine all the scientific disciplines, it can be seen from the verses of the Qur'an which was ordered to examine the nature and seisinya. Religious Humanist Values education which leads to the study of the komprehenshif of good science is both religious and General Education Development Concept is as Islam that humanizing of man in accordance with the duties of man as abdullah and the Caliph in the face of the Earth.